Physical and Microbiology Characterization of Chicken Sausage that Added by Oyster Mushroom - Yulianto, Wahid; Malta, Lilik; Bulkaini, Bulkaini; Kisworo, Djoko; Haryanto, Haryanto; Dewi Wulandani, Baiq Rani; Fahrullah, Fahrullah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Oyster mushrooms are a healthy alternative food source for reducing the fat content of sausages due to their low fat content. Chicken sausage is a processed meat product that typically contains meat, binders, and fillers. This study aimed to investigate the physical and microbiological properties of chicken sausage with varying concentrations of oyster mushrooms, which are added to improve its quality. The study employed a completely randomized design with three treatments. If a treatment showed a difference, the Duncan Multiple Range Test was conducted. The treatments consisted of J0: 0% oyster mushroom, J1: 1% oyster mushroom, and J2: 2% oyster mushroom. Statistically, the use of different concentrations of oyster mushrooms did not result in a significant difference (P>0.05) in the water binding capacity, breaking power, pH, and total plate count of chicken sausages. However, the addition of oyster mushroom concentrations can improve the physical and microbiological quality of the sausages. The addition of different concentrations of oyster mushroom to chicken meat sausage resulted in a water binding capacity of 39.28-46.12%, breaking strength of 0.4-0.5 kg/cm2, pH value of 6.46-6.56, and total plate count of 1.57-1.86 cfu/g. The treatment that yields the highest water binding capacity (45.06%), breaking power (0.04 kg/cm2), pH (6.56), and total plate count (1.57 cfu/g) is the addition of 1% oyster mushroom concentration. The concentration of oyster mushroom used in the preparation of chicken meat sausages should not exceed 1% of the total sausage mixture.